MODELING AND DESIGN OF DYNAMIC MOVEMENT CONTROL SYSTEMS INCLINED PLATFORM LIFTS FOR PERSONS WITH DISABILITIES - Ramadhany Hakim, Gilang
This study aims to discuss the importance of modeling and designing a dynamic control system for an inclined platform lift (IPL) to meet the specific needs of people with disabilities, in accordance with government regulations, such as Law No. 13 of 2020. The research method used in this study is the design of a PID controller to control the speed of movement of the IPL, even with load variations. Modeling of the IPL’s movement and dynamic actuator modeling were carried out to support the research. The results showed that the movement response using a PID controller with kp = 1 and ki = 1 was much better, resulting in a stable movement speed and an error of 0, and a movement speed that complied with the international/national regulation ASME A18.1 of 0.15 m/s. the results of this study can help improve the design of the dynamic control system for an IPL to meet international/national regulatory standards.